2020
DOI: 10.1210/clinem/dgaa039
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates and Sex Steroid Hormones Among Men From NHANES, 2013–2016

Abstract: Context Phthalates are commonly found in commercial packaging, solvents, vinyl, and personal care products, and there is concern for potential endocrine-disrupting effects in males. The commonly used di-2-ethylhexyl phthalate (DEHP) has progressively been replaced by seldom studied compounds, such as bis-2-ethylhexyl terephthalate and 1,2-cyclohexane dicarboxylic acid di-isononyl ester (DINCH). Objective To investigate the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 50 publications
2
27
1
Order By: Relevance
“…Similarly, in men with benign prostatic hyperplasia, estradiol levels, testosterone and steroidogenic enzymes aromatase, and 5α-reductase were increased [ 107 ]. Other studies observed associations between postnatal exposure to phthalates in healthy and infertile men and decreased testosterone [ 80 , 194 , 195 , 196 , 197 , 198 ]. Epidemiological studies yielded some conflicting results in the association between phthalate exposure and estradiol levels in men.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
“…Similarly, in men with benign prostatic hyperplasia, estradiol levels, testosterone and steroidogenic enzymes aromatase, and 5α-reductase were increased [ 107 ]. Other studies observed associations between postnatal exposure to phthalates in healthy and infertile men and decreased testosterone [ 80 , 194 , 195 , 196 , 197 , 198 ]. Epidemiological studies yielded some conflicting results in the association between phthalate exposure and estradiol levels in men.…”
Section: Hormonal Mechanisms Of Phthalates’ Action On Reproductivementioning
confidence: 99%
“…Many phthalates, even at a low concentration, are known endocrine disruptors ( Figure 3 ) that have an influence on the development of organisms and their reproductive system [ 33 ]. For instance, PAEs have been recognized to induce changes in oxidative stress, disturb sex hormone balances, which can decrease fertility and increase the rate of reproductive defects and malformations [ 33 , 34 , 35 , 36 ]. Interference with testosterone activity, especially early in life, can have irreversible effects on male reproduction [ 37 ].…”
Section: Phthalates Backgroundmentioning
confidence: 99%
“…As indicated by the name, FAI is not an estimate of the free testosterone concentration but simply an index of the balance between serum testosterone and SHBG. While it is recognized that FAI is not based on any biophysical characterization, it continues to be used by investigators ( 9 , 10 ). Several algorithms based on law-of-mass-action equations requiring information on the level of TT and SHBG have been developed with varying degree of correlation with equilibrium dialysis and some have been suggested as reasonable alternatives to direct measurements ( 1 ).…”
Section: Introductionmentioning
confidence: 99%